التحول من متطلبات بازل ( I ) إلى متطلبات بازل ( II ) حالة دراسية لمصارف عربية مختارة للمدة 2005 – 2009 (المجلة العراقية للعلوم الاقتصادية, 2018)
The standard of the efficiency of capital is one of the important standards which banks care of . Its importance increased with the risks facing banks , this necessitates effective control over banks to know to what extent the bank can endure these risks through possessing enough capital to endure risks facing the banking sector . This is lied behind the importance of possessing least enough capital which is stated by Basel Committee and adopted by the majority of Arabic states which is known Basel ( I ) . Due to the increased risks facing banks was one of the important reasons behind moving to Basel ( II ) . of the important consideration regarded by Basel ( II ) was the addition of operational risks to the equation of the efficiency of the Capital . So the research is written to answer the following question , Does Arabian Banks have enough financial and human resources and enough time for application of Basel ( II ) , or they were unable to achieve that . The research concluded a set of conclusions and recommendations the most important of them is the commitment of Arabian Banks to apply capital efficiency standard according to the requirements of Basel ( II ) though they are not of legal commitment nature . Moreover Arabian Banks possessed physical and human abilities needed for applying the requirements of Basel ( II ) regarding the efficiency of capital in nearly an early time compared with the Banks in advanced states . The moving form Basel ( I ) to Basel ( II ) is a complete transformation for risk management concept , and Arabian Banks have to apply Basel ( II ) completely in order to be able to face financial crises . Moreover Arabic Banks have to apply the simplified methods to calculate operational risks before moving to the advanced methods , Arabian Banks have too , to publish studies based on evaluating Basel ( II ) and its effects on Arabian Banks , and determining the weaknesses if any in order to correct them .